Kinerja Load Balancing dengan Menggunakan Metode Per Connection Classifier - Denis Taslim; Iskandar Fitri; Rini Nuraini (KITA Institute, 2020)
The internet connection used in the computer laboratory must be protected from all kinds of interference. One way to do this is by means of Load balancing with the Per Connection Classifier (PCC) method. The research results show that the proposed load balancing technique becomes a balanced traffic load on each ISP or gateway so that bandwidth usage is more efficient and able to speed up internet network connections. It also proposes a failover technique to help reduce internet network connections where connection failures occur on one of the ISP lines. In testing and packet Loss and Throughput each 6 stages have been carried out. Namely with the results obtained from testing the Loss package 10, 20, 30, 40, 50, 60 minutes. For the throughput test results, namely by measuring from 10, 20, 30, 40, 50, 60 minutes. The test refers to the TIPHONE version.